Tripartite PLKI-ECRL Agreement to benefit Rail Industry and NRCOE - Nur Laila, Afandi (2017)
Putrajaya, 2 November- The inking of a tripartite Memorandum of Agreement (MoA) to formalize the implementation of the ECRL Industrial Skills Training Programme (PLKI-ECRL), will nurture more skilled workers to be in the rail industry and complement the establishment of the National Rail Centre of Excellence (NRCOE).